2001
DOI: 10.1002/mar.1043
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of subjective age biases among senior women

Abstract: From a conceptual framework based on developmental psychology and mechanisms of social comparison, this research proposes testing an explanatory model of the trend to see oneself as younger which is characteristic of seniors. The identification of antecedent variables of this tendency suggests a new approach to segmenting the feminine over fifties market in France.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0
8

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 41 publications
4
48
0
8
Order By: Relevance
“…This observation is in line with researchers' theorizing that a younger relative subjective age can be seen "as a special case of self-enhancement, since to feel, look, and act young is generally considered to be something positive" (Teuscher, 2009, p. 23; see also Guiot, 2001). Studies have shown that such age-related self-enhancement may have benefits in terms of health, vitality, and productivity (Montepare, 2009;Stephan et al, 2012).…”
Section: Relative Subjective Age In Organizationssupporting
confidence: 80%
See 1 more Smart Citation
“…This observation is in line with researchers' theorizing that a younger relative subjective age can be seen "as a special case of self-enhancement, since to feel, look, and act young is generally considered to be something positive" (Teuscher, 2009, p. 23; see also Guiot, 2001). Studies have shown that such age-related self-enhancement may have benefits in terms of health, vitality, and productivity (Montepare, 2009;Stephan et al, 2012).…”
Section: Relative Subjective Age In Organizationssupporting
confidence: 80%
“…The subjective age was measured by asking each employee how old he or she feels independently of his or her real age (Caudroit, Stephan, Chalabaev, & Le Scanff, 2012;Westerhof, Barrett, & Steverink, 2003). For the subjective age measure, the chronological age was subtracted from the subjective age (i.e., Barnes-Farrell & Piotrowski, 1989;Guiot, 2001;Stephan et al, 2012). A negative value indicated that an employee felt younger compared with his or her chronological age, and a positive value indicated that an employee felt older compared with his or her chronological age.…”
Section: Methodsmentioning
confidence: 99%
“…(34-36) Uotinen (1998)(34) in a comparison of North American and Finnish men and women found that North Americans identified with a more youthful age identity compared to the Finnish group. Guiot (2001) (36) and Barak (2001) (35) respectively found that the French and East Asians also identified with a more youthful age group. This was found to be consistent with the PRAP focus group findings.…”
Section: Discussionmentioning
confidence: 90%
“…The desired age of individuals during late adulthood tends to be more than eight years younger than their chronological age (Guiot 2001). This notion is in line with the theory of continuity (Atchley 1993), which states that seniors intend to conserve the same aptitudes and physical, mental or social capacities as when they were younger.…”
Section: Moderating Effect Of Actual Agementioning
confidence: 99%
“…Adults aged 21 to 84 Life events Guiot (2001) Examines the antecedents that influence a youthful bias of senior women towards a younger cognitive age.…”
Section: No Sample Theory Articlementioning
confidence: 99%